2020
DOI: 10.3390/ijms21165645
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Melatonin on Neurogenesis Impairment in Neurological Disorders and Its Relevant Molecular Mechanisms

Abstract: Neurogenesis is the process by which functional new neurons are generated from the neural stem cells (NSCs) or neural progenitor cells (NPCs). Increasing lines of evidence show that neurogenesis impairment is involved in different neurological illnesses, including mood disorders, neurogenerative diseases, and central nervous system (CNS) injuries. Since reversing neurogenesis impairment was found to improve neurological outcomes in the pathological conditions, it is speculated that modulating neurogenesis is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 126 publications
(154 reference statements)
3
30
0
Order By: Relevance
“…Several of these function in development, morphology ( wnt4, wnt11f2, irx2a, msx2b , sox19a , tbx5a) [ 111 , 112 , 113 , 114 , 115 , 116 ] and cell proliferation (msx2b ) [ 117 ]. Other genes belonging to torpor_NET_only function in neurogenesis (Foxi1, irx2a, sox19a ) [ 118 , 119 ], neuron differentiation ( emx3, lmx1bb ) [ 120 , 121 ], synaptic function ( sncga ) [ 122 ] and plasticity ( pcp4a ) [ 123 , 124 ] which may be globally upregulated in response to the melatonin which has previously been associated with promoting neurogenesis [ 125 , 126 ]. Upregulation of stem cell, developmental and proliferative genes might offer protective affects by increasing cell survival and ensuring correct morphology during cell replacement responses, while those genes involved in neuronal development should be investigated further for signs of neuroprotective affects in situ .…”
Section: Resultsmentioning
confidence: 99%
“…Several of these function in development, morphology ( wnt4, wnt11f2, irx2a, msx2b , sox19a , tbx5a) [ 111 , 112 , 113 , 114 , 115 , 116 ] and cell proliferation (msx2b ) [ 117 ]. Other genes belonging to torpor_NET_only function in neurogenesis (Foxi1, irx2a, sox19a ) [ 118 , 119 ], neuron differentiation ( emx3, lmx1bb ) [ 120 , 121 ], synaptic function ( sncga ) [ 122 ] and plasticity ( pcp4a ) [ 123 , 124 ] which may be globally upregulated in response to the melatonin which has previously been associated with promoting neurogenesis [ 125 , 126 ]. Upregulation of stem cell, developmental and proliferative genes might offer protective affects by increasing cell survival and ensuring correct morphology during cell replacement responses, while those genes involved in neuronal development should be investigated further for signs of neuroprotective affects in situ .…”
Section: Resultsmentioning
confidence: 99%
“…Second, as molecular mechanisms regarding the protective effects of melatonin in the collagenase-induced model remain poorly understood and melatonin possesses anti-microglial activation property, the effects of melatonin on different microglial-related inflammatory pathways can be investigated in this ICH model. Third, the role of melatonin in enhancing recovery after ICH via promoting endogenous neurogenesis can be explored in the collagenase-induced model because recent studies showed that melatonin protected against different neurological diseases by stimulation of endogenous neurogenesis (26).…”
Section: Discussionmentioning
confidence: 99%
“…Attributing to its direct antioxidant, anti-inflammatory, and anti-apoptotic properties, melatonin is a neuroprotective molecule against different neurological diseases (23)(24)(25). Recent studies have also uncovered its functions on neurogenesis promotion (26).…”
Section: Introductionmentioning
confidence: 99%
“…Restoring rhythmicity via chronotherapy may ameliorate the symptoms of myriad neurological disorders that involve aberrant adult neurogenesis (Albrecht, 2017; Leung et al., 2020; McClung, 2013; Schnell, Albrecht, et al., 2014). In this regard, the circadian hormone melatonin appears to be a very promising therapeutic candidate for depression, Alzheimer's disease, neurodegenerative diseases and CNS injuries (Leung et al., 2020; Mihardja et al., 2020; Song, 2019; Valdes‐Tovar et al., 2018). In vitro, melatonin promoted survival of new neurons derived from hippocampal NSPCs, and increased survival of NSCPs and post‐mitotic immature neurons, which may explain its antidepressant effects in the Porsolt swim test (Ramirez‐Rodriguez et al., 2009).…”
Section: Circadian Control Of Stem Cell Behaviourmentioning
confidence: 99%